2014
DOI: 10.3389/fpubh.2014.00120
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine for Epilepsy Support in Resource-Poor Settings

Abstract: The Problem: Epilepsy is a common disease worldwide causing significant physical and social disability. It is one of the most treatable neurological diseases. Yet, in rural, poorer countries like much of India and Nepal, most people with epilepsy are not undergoing any treatment often because they cannot access doctors.Conventional Approaches: It is being appreciated that perhaps doctors are not the solution and that enabling health workers to treat epilepsy may be better. Few details, however, have been put f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 18 publications
1
21
0
1
Order By: Relevance
“…The Epilepsy Foundation reports that the epilepsy incidence rate reaches as high as 1/26, 70% of which can be controlled via timely treatment and control. Telemedicine plays an important role in the treatment and follow-up of patients with epilepsy, especially those in remote areas [51]. Epilepsy is a random phenomenon that occurs without warning.…”
Section: Epilepsymentioning
confidence: 99%
“…The Epilepsy Foundation reports that the epilepsy incidence rate reaches as high as 1/26, 70% of which can be controlled via timely treatment and control. Telemedicine plays an important role in the treatment and follow-up of patients with epilepsy, especially those in remote areas [51]. Epilepsy is a random phenomenon that occurs without warning.…”
Section: Epilepsymentioning
confidence: 99%
“…Review identified many reasons behind the lack of accessibility, such as poor communication system, land slide or flash flood during rainy season, etc. In total 20 papers reported the telemedicine features of addressing challenges of geographic remoteness [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] and 11 papers reported time saving [29][30][31][32][33]40,41,[47][48][49][50] character. 4 papers reported communication and transportation 30,32,46,49 related issues.…”
Section: Theme 1: Geographic Difficulties and Emergency Contextmentioning
confidence: 99%
“…Smartphone-based service Patterson et al 2014 43 Epilepsy patients in rural areas in Nepal are mostly deprived of any treatment, because of inadequate doctors and health facilities. Telemedicine program was initiated to overcome these shortcomings.…”
Section: Videoconferencing and Teleconsultationmentioning
confidence: 99%
“…During the past decade or so, many health care professionals and physicians around the world have developed or proposed creative ways to overcome the challenges and to provide better care for patients with epilepsy in resource-limited settings. 4,5 These kinds of actions have often resulted in significant changes regionally. 4 However, poor income, lack of resources, regulatory approval, and high prices are apparently not the only factors that play significant roles in lack of access to AEDs and appropriate epilepsy care.…”
Section: To the Editorsmentioning
confidence: 99%